ARNALDO ANTUNES’ POETICS “PALAVRA” - de Paula, Luciane (Laboratório Editorial FCL-UNESP, 2010)
This article reflects on Arnaldo Antunes‟ (AA) poetics. For this purpose, both the contributions of Fontanille and Zilberberg regarding tensivity, as well as some ideas of Tatit regarding song semiotics. The aim is to think about how the dance between enunciation and enunciate is structured in AA within poetical architecture as exemplified here based on the analysis of the poem “Palavra”. The hypothesis is that the tension between the two central nuclei of the poem, metalanguage and erotism, are the essential compositional marc of AA poetical stylistics. The results lead to the reflection that the musical tension is the game that guarantees the movement between the density of the word and the erotic fluidity of the authorial (metalinguistic) act of production.